2015
DOI: 10.1099/mic.0.000059
|View full text |Cite
|
Sign up to set email alerts
|

Human neutrophils produce extracellular traps against Paracoccidioides brasiliensis

Abstract: Neutrophils play an important role as effector cells and contribute to the resistance of the host against microbial pathogens. Neutrophils are able to produce extracellular traps (NETs) in response to medically important fungi, including Aspergillus spp., Candida albicans and Cryptococcus gattii. However, NET production in response to Paracoccidioides brasiliensis has yet to be studied. We have demonstrated that human neutrophils produce NETs against both conidia and yeasts of P. brasiliensis. Although the NAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
2
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 53 publications
2
29
2
4
Order By: Relevance
“…However, more prominent results in relation to involvement of both mechanisms were found when cells were activated with either GM-CSF, IFN-␥ or TNF-␣¸ a strategy to get significant increase in total fungicidal activity (Rodrigues et al, 2007). Contrasting with our results, Mejía et al (2015) in a recent study, showed that NETs are not involving in P. brasiliensis killing. These differences can be explained by the experimental design used.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…However, more prominent results in relation to involvement of both mechanisms were found when cells were activated with either GM-CSF, IFN-␥ or TNF-␣¸ a strategy to get significant increase in total fungicidal activity (Rodrigues et al, 2007). Contrasting with our results, Mejía et al (2015) in a recent study, showed that NETs are not involving in P. brasiliensis killing. These differences can be explained by the experimental design used.…”
Section: Discussioncontrasting
confidence: 86%
“…High concentrations of these components in NETs, as well as their synergistic actions are responsible for the effective antimicrobial activity of these structures (Brinkmann and Zychlinsky, 2012). Recently, NETs release induced by P. brasiliensis was reported (Mejía et al, 2015;Della Coleta et al, 2015). Here, by using scanning electron microscopy we confirmed that P. brasiliensis virulent strain (P. brasiliensis 18) induces neutrophils to release NETs and that dectin-1 receptor is the main PRR involved in this process.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…In the original NET description, cytochalasin D effectively prevented phagocytosis of Shigella flexneri or S. aureus but not NET release [5]. Other studies have also reported that cytoskeletal inhibitors had no effect on NET formation in response to Paracoccidioides brasiliensis or gold nanoparticles [49,50]. Neeli et al [51] reported that a 10 μM treatment with either the microtubule inhibitor nocodazole or cytochalasin D diminished histone deamination and NET release in response to LPS, and similar results were documented by Jerjomiceva et al [52] using enrofloxacin-treated bovine neutrophils.…”
Section: Cellular Pathways Implicated In Met Releasementioning
confidence: 99%
“…Further fungicidal effects have been reported for both yeast and hyphal forms of C. albicans [120]. NETosis has also been observed in response to Cryptococcus neoformans [121] and Paracoccidioides brasiliensis [122]. …”
Section: Interaction Of Human Pathogenic Fungi With Neutrophilsmentioning
confidence: 99%